THE EFFECT OF FIVE-FINGER HYPNOTHERAPY ON REDUCING ANXIETY LEVELS DURING DAILY EXAMINATIONS IN ADOLESCENTS - Wulanningrum, Dian Nur; Suryandari, Selvy Sri Dewi; Yulianto, Sigit; Putri, Diyanah Syolihan Rinjani (Journal of Advanced Nursing and Health Sciences, 2026)
Background: Adolescence is a transitional period from childhood to adulthood characterized by comprehensive changes. During this stage of development, adolescents face many challenges, including the emergence of feelings of anxiety. The daily examination process creates a mental burden for students. This condition becomes a major source of academic pressure and triggers academic anxiety. One non-pharmacological therapy that can reduce anxiety is the Five-Finger Hypnotherapy technique. The objective of this study is to determine the effect of the Five-Finger Hypnotherapy therapy on reducing anxiety levels in adolescents when facing daily examinations.Methods: This study used a quasi-experimental design with a pre-test and post-test approach. The research was conducted at SMA N 2 Boyolali in April 2025, involving 74 students as respondents. The sampling technique used was purposive sampling. The research instrument was a questionnaire. Data analysis was performed using the Wilcoxon test.Results: The results showed that before the Five-Finger Hypnotherapy therapy was administered, 35 respondents (47.3%) experienced moderate anxiety, and 35 respondents (47.3%) experienced severe anxiety. After the therapy was given, 52 respondents (70.3%) were categorized as having no anxiety. The analysis results indicated a significant difference in anxiety levels before and after the Five-Finger Hypnotherapy therapy, with a p-value < 0.001. Conclusion: The Five-Finger Hypnotherapy therapy was proven to have a significant effect in reducing anxiety levels among adolescents facing daily examinations.